Ruthenium-doped nickel-based catalyst electrode and preparation method and application thereof
By forming a porous nickel oxyhydroxide catalytic layer on the Raney nickel catalyst and doping it with ruthenium element, the problem of insufficient stability and catalytic activity of the catalyst under high current density in the existing technology is solved, and efficient and stable electrolytic water production is achieved. hydrogen.
Patent Information
- Application Number
- CN202411551733.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-24
AI Technical Summary
The existing Rainey nickel catalyst cannot achieve long-term stable hydrogen production under high current density, mainly due to insufficient catalytic activity and weak interface binding force with the base nickel mesh.
A mixture of ethylene glycol and glycerin is used as the solvent and water is used as the reaction medium. A porous nickel oxyhydroxide catalytic layer is formed through anodization. On this basis, the ruthenium-doped nickel-based catalyst is prepared by impregnating the ruthenium element.
The catalytic activity and stability of the ruthenium-doped nickel-based catalyst are significantly improved, especially the long-term stable hydrogen production performance at high current density is achieved, effectively reducing the energy consumption and cost of hydrogen production by electrolyzing water.
Smart Images

Figure CN119352064A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode preparation, and specifically relates to a ruthenium-doped nickel-based catalyst electrode and a preparation method and application thereof. Background Art
[0002] In the context of addressing global climate change and achieving energy transformation, green hydrogen, as a clean and efficient energy source, will become an ideal choice to replace fossil fuels. Hydrogen production by water electrolysis is considered to be the best way to obtain green hydrogen energy. Alkaline water electrolysis hydrogen production technology is currently a relatively mature technology and has been used on a large commercial scale. However, with the development of technology and the increase in demand, it has become an industry consensus to achieve long-term and stable hydrogen production at high current density. This trend has put forward more stringent requirements on the stability of the catalyst.
[0003] The water electrolysis process includes two half reactions, namely the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). In order to improve the efficiency of hydrogen production by water electrolysis, the development of HER and OER catalysts is extremely critical to reduce the energy consumption and cost of water electrolysis. The Raney nickel catalyst obtained by the existing preparation method cannot meet the requirements of stable hydrogen production under high current. The main limitation lies in the catalytic activity of the Raney nickel catalyst itself and the interfacial bonding strength between it and the base nickel mesh. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a ruthenium-doped nickel-based catalyst electrode and a preparation method and application thereof. The present invention uses a mixed solution of ethylene glycol and glycerol as a solvent and water as a reaction medium. Through an anodizing method, a fluorine-containing ion salt is used to etch on a nickel-based substrate to form a porous nickel hydroxide oxidized catalyst layer to obtain a nickel-based catalyst electrode; then the nickel-based catalyst electrode is immersed in a ruthenium element-containing solution. During the immersion process, ruthenium ions are replaced and doped with nickel ions in the porous nickel hydroxide oxidized layer to obtain a ruthenium-doped nickel-based catalyst electrode. The preparation method of the present invention is not only simple in process, mild in conditions, and easy to scale up production, but also significantly improves the catalytic activity and stability of the ruthenium-doped nickel-based catalyst, especially achieves long-term stable hydrogen production performance at high current density, and effectively reduces the energy consumption and cost of hydrogen production by electrolysis of water.
[0005] In order to achieve the above purpose, the technical solution adopted in this application is:
[0006] The first object of the present invention is to provide a method for preparing a ruthenium-doped nickel-based catalyst electrode, comprising the following steps:
[0007] S1. Dissolving a fluoride-containing ion salt in a mixture of ethylene glycol and glycerol, and then mixing with water to obtain an anodizing solution; wherein the volume ratio of the ethylene glycol to the glycerol is 1:2-4; the concentration of the fluoride-containing ion salt in the anodizing solution is 0.25 mol / L-0.8 mol / L; when the concentration of the fluoride-containing ion salt in the anodizing solution is high, the etching degree of the surface of the nickel-based substrate will be aggravated, resulting in excessive etching or irregular etching; conversely, the etching degree of the surface of the nickel-based substrate will be weakened, resulting in insufficient formation of a porous nickel hydroxide oxycatalytic layer.
[0008] S2. Place the nickel-based substrate in an anodizing solution for anodizing treatment. During the anodizing process, the nickel atoms on the surface of the nickel-based substrate combine with the hydroxide ions in the anodizing solution under the etching of the fluorine-containing salt and the oxidation of the electric field, thereby forming a porous nickel oxide catalyst layer on the surface of the nickel-based substrate to obtain a nickel-based catalyst electrode.
[0009] S3. Immersing the nickel-based catalyst electrode in a solution containing ruthenium elements, the ruthenium ions are replaced and doped with the nickel ions in the porous nickel hydroxide oxycatalytic layer, and drying to obtain a ruthenium-doped nickel-based catalyst electrode.
[0010] Preferably, the fluoride-containing ion salt is selected from one or both of ammonium fluoride and sodium fluoride.
[0011] Preferably, the nickel-based substrate is selected from nickel mesh, nickel foam, nickel plate or metallic nickel.
[0012] Preferably, the anodizing method is: using anodizing solution as electrolyte, a nickel-based substrate as anode, a platinum sheet as cathode, connecting a DC regulated power supply, and using a single-chamber electrolytic cell to anodize the nickel-based substrate to obtain a nickel-based catalyst electrode.
[0013] Preferably, the anodizing treatment conditions are: anodizing treatment at 0°C to 20°C and 20V to 50V for 1h to 8h; wherein, higher temperature and voltage will aggravate the etching degree of the surface of the nickel-based substrate and promote the formation of the porous nickel oxyhydroxide catalyst layer, but too high temperature and voltage will lead to excessive etching or irregular etching, thereby affecting the performance and stability of the catalyst electrode. On the contrary, too low temperature and voltage will lead to insufficient etching and insufficient growth of the pore structure, which will also affect the catalytic activity of the ruthenium-doped nickel-based catalyst electrode.
[0014] More preferably, the anodizing treatment conditions are: anodizing at 10° C. and 50 V for 1 hour.
[0015] Preferably, the nickel-based substrate is also subjected to an acid treatment before anodizing in order to remove the oxide layer on the surface.
[0016] Preferably, the concentration of the ruthenium element solution is 5 mmol / L to 10 mmol / L.
[0017] Preferably, the ruthenium-containing solution is selected from RuCl3 solution.
[0018] More preferably, the solubility of the RuCl3 solution is 5 mmol / L.
[0019] Preferably, the immersion time is 12 h to 48 h.
[0020] Preferably, the drying conditions are: drying at 20°C to 60°C for 6h to 24h.
[0021] The second object of the present invention is to provide a ruthenium-doped nickel-based catalyst electrode prepared by the above-mentioned preparation method, wherein the ruthenium-doped nickel-based catalyst electrode is composed of a ruthenium-doped nickel-based catalyst and a nickel-based substrate, and the ruthenium-doped nickel-based catalyst is loaded on the nickel-based substrate.
[0022] The third object of the present invention is to provide the use of the above-mentioned ruthenium-doped nickel-based catalyst electrode in the preparation of a cathode hydrogen evolution electrode and an anode oxygen evolution electrode.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention provides a method for preparing a ruthenium-doped nickel-based catalyst electrode. The method comprises the following steps: firstly mixing ethylene glycol, glycerol, water and a fluorine-containing ion salt to obtain an anodizing solution; wherein the volume ratio of the ethylene glycol to the glycerol is 1:2-4; and the concentration of the fluorine-containing ion salt in the anodizing solution is 0.25 mol / L-0.8 mol / L; then placing a nickel-based substrate in the anodizing solution for anodizing treatment. During the anodizing treatment, nickel atoms on the surface of the nickel-based substrate are combined with hydroxide ions in the anodizing solution under the etching of the fluorine-containing ion salt and the oxidation of the electric field to form a porous hydroxy-nickel oxide catalyst layer on the surface of the nickel-based substrate to obtain a nickel-based catalyst electrode; finally, the nickel-based catalyst electrode is immersed in a ruthenium element solution. During the immersion process, ruthenium ions are replaced and doped with nickel ions in the porous hydroxy-nickel oxide catalyst layer. After drying, a ruthenium-doped nickel-based catalyst electrode is obtained. The preparation method of the present invention not only has simple process, mild conditions, and is easy to scale up for production, but also significantly improves the catalytic activity and stability of the ruthenium-doped nickel-based catalyst, especially achieves long-term stable hydrogen production performance under high current density, and effectively reduces the energy consumption and cost of hydrogen production by electrolysis of water.
[0025] Among them, during the anodizing process, since the nickel-based substrate in the aqueous solution mainly participates in the electrolysis of water, a small amount of water is added on the basis of ethylene glycol and glycerol, which not only ensures the conductivity of the anodizing solution, but also avoids the nickel-based substrate being consumed too quickly due to the electrolysis of water; the fluorine-containing ion salt is mainly used to etch the nickel-based substrate, and the nickel atoms on the surface of the nickel-based substrate are combined with the hydroxide ions in the anodizing solution under the etching of the fluorine-containing ion salt and the oxidation action of the electric field to form nickel oxyhydroxide (NiOOH); as the anodizing process proceeds, a porous nickel oxyhydroxide catalyst layer is formed on the surface of the nickel-based substrate; by immersing the nickel-based catalyst electrode in a ruthenium-containing solution, the replacement doping process of ruthenium ions with nickel ions in the porous nickel oxyhydroxide catalyst layer is realized to obtain a ruthenium-doped nickel-based catalyst electrode, which significantly enhances the binding force between the ruthenium-doped nickel-based catalyst and the nickel-based substrate and promotes stable performance.
[0026] In addition, the ruthenium-doped nickel-based catalyst electrode prepared by the present invention has dual-functional properties. On the porous nickel oxyhydroxide catalyst layer doped with ruthenium, ruthenium atoms show a strong adsorption ability for water molecules (H2O), which greatly promotes the generation of adsorbed hydrogen atoms (H atoms). At the same time, the hydrogen adsorption free energy of nickel atoms is extremely close to the ideal state, which is crucial for the desorption of hydrogen and the effective release of hydrogen. In addition, the interface structure of the porous nickel oxyhydroxide catalyst layer also promotes the OOH - ions, which in turn accelerates the oxygen release process. These two mechanisms work together to significantly enhance the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) of the electrode, enabling it to simultaneously and efficiently carry out HER and OER under alkaline conditions.
[0027] 2. The ruthenium-doped nickel-based catalyst electrode provided by the present invention has good long-term stable operation capability at 1000mA / cm 2 At a current density of 100 mA / cm2, it can operate continuously and stably for up to 500 h. At the same time, the ruthenium-doped nickel-based catalyst electrode has excellent catalytic performance. In a 1 mol / L potassium hydroxide solution, when the current density reaches 100 mA / cm2, 2 When the ruthenium-doped nickel-based catalyst electrode is used, the hydrogen production overpotential is only 81mV, while the oxygen production overpotential is only 490mV, which significantly improves the efficiency of hydrogen production by water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an electron microscope image of the nickel-based catalyst electrode in Example 1 of the present invention.
[0029] Figure 2LSV curves of HER of NM, ANM, ANM-Ru-48 prepared in Example 1 of the present invention and ANM-Ru-24 prepared in Example 6 and their corresponding overpotential diagrams, wherein (a) is the LSV curve diagram of HER of NM, ANM, ANM-Ru-48 prepared in Example 1 and ANM-Ru-24 prepared in Example 6, and (b) is the overpotential diagram of HER of NM, ANM, ANM-Ru-24 and ANM-Ru-48.
[0030] Figure 3 LSV curves of OER of NM, ANM, ANM-Ru-48 prepared in Example 1 of the present invention and ANM-Ru-24 prepared in Example 6 and their corresponding overpotential diagrams, wherein (a) is the LSV curve diagram of OER of NM, ANM, ANM-Ru-48 prepared in Example 1 and ANM-Ru-24 prepared in Example 6, and (b) is the overpotential diagram of OER of NM, ANM, ANM-Ru-48 prepared in Example 1 and ANM-Ru-24 prepared in Example 6.
[0031] Figure 4 The ruthenium-doped nickel-based catalyst electrode in Example 1 of the present invention is used as the anode and cathode at 1000 mA / cm 2 Voltage-time diagram for water electrolysis at different current densities. DETAILED DESCRIPTION
[0032] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0033] Raney nickel catalysts prepared by existing technologies, as a commonly used catalyst in the field of hydrogen production by water electrolysis, can promote the hydrogen evolution reaction, but still have obvious deficiencies in stability and catalytic activity at high current density. Its main limitation is that the catalytic activity of the catalyst itself is not enough to support the long-term stable hydrogen production needs, and the interface bonding force between the catalyst and the base nickel mesh is weak, resulting in the detachment of the catalyst or a significant decrease in performance during the long-term electrolysis process, thereby limiting the further improvement of the efficiency of hydrogen production by water electrolysis.
[0034] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a ruthenium-doped nickel-based catalyst electrode, comprising the following steps: dissolving a fluorine-containing ion salt in a mixed solution of ethylene glycol and glycerol, and then mixing with water to obtain an anodizing solution; wherein the volume ratio of the ethylene glycol to the glycerol is 1:2-4; the concentration of the fluorine-containing ion salt in the anodizing solution is 0.25 mol / L-0.8 mol / L; placing a nickel-based substrate in the anodizing solution for anodizing treatment, during the anodizing treatment, nickel atoms on the surface of the nickel-based substrate are combined with hydroxide ions in the anodizing solution under the etching of the fluorine-containing ion salt and the oxidation action of the electric field, forming a porous hydroxy-nickel oxide catalyst layer on the surface of the nickel-based substrate to obtain a nickel-based catalyst electrode; immersing the nickel-based catalyst electrode in a solution containing ruthenium element, during the immersion process, ruthenium ions are replaced and doped with nickel ions in the porous hydroxy-nickel oxide catalyst layer, and drying to obtain a ruthenium-doped nickel-based catalyst electrode.
[0035] Among them, the present invention combines anodizing treatment with the strategy of ruthenium element impregnation and replacement, utilizes fluorine-containing ion salt to etch the nickel-based substrate to form a porous nickel hydroxide oxycatalytic layer, and regulates the intensity of the etching reaction by an aqueous solution, thereby significantly enhancing the binding force between the ruthenium-doped nickel-based catalyst and the electrode substrate as well as the catalytic activity and stability. At the same time, the strong adsorption ability of ruthenium atoms for water molecules and the nearly ideal hydrogen adsorption free energy of nickel atoms are utilized to synergistically promote the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER), thereby overcoming the problem of insufficient stability and catalytic activity of the Raney nickel catalyst at high current density in the prior art.
[0036] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0037] Example 1
[0038] A method for preparing a ruthenium-doped nickel-based catalyst electrode comprises the following steps:
[0039] S1. A nickel mesh with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel mesh was rinsed with deionized water until the pH was 7. The washed nickel mesh was stored in anhydrous ethanol for later use, and the nickel mesh was recorded as NM.
[0040] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.54 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0041] S3. In a double-electrode electrolytic cell, the nickel mesh is used as the anode and the platinum sheet is used as the cathode to anodize the nickel mesh; a DC regulated power supply is used to control the anodizing voltage to 50 V and anodize for 1 hour; during the anodizing process, condensed water is used to control the temperature of the anodizing solution at 10°C to obtain a nickel-based catalyst electrode, recorded as ANM; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0042] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 48 hours, rinse it with deionized water, and dry it in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode (ANM-Ru), which is recorded as ANM-Ru-48.
[0043] The ruthenium-doped nickel-based catalyst electrode was 2 The overpotential for hydrogen production under current density is only 80.9 mV, and the overpotential for oxygen production is 490.2 mV.
[0044] Example 2
[0045] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S2, the concentration of ammonium fluoride is replaced from 0.54 mol / L to 0.27 mol / L, comprising the following steps:
[0046] S1. A nickel mesh with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel mesh was rinsed with deionized water until the pH value was 7. The washed nickel mesh was stored in anhydrous ethanol for later use.
[0047] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.27 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0048] S3. In a double-electrode electrolytic cell, the nickel mesh is used as the anode and the platinum sheet is used as the cathode to anodize the nickel mesh; a DC regulated power supply is used to control the anodizing voltage to 50V, and the anodizing is performed for 1 hour; during the anodizing process, condensed water is used to control the temperature of the anodizing solution at 10°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0049] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 48 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0050] Example 3
[0051] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S2, the concentration of ammonium fluoride is replaced from 0.54 mol / L to 0.08 mol / L, comprising the following steps:
[0052] S1. A nickel mesh with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel mesh was rinsed with deionized water until the pH value was 7. The washed nickel mesh was stored in anhydrous ethanol for later use.
[0053] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.08 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0054] S3. In a double-electrode electrolytic cell, the nickel mesh is used as the anode and the platinum sheet is used as the cathode. The nickel mesh is anodized by anodization method; a DC regulated power supply is used to control the anodization voltage to 50V, and the anodization is performed for 1 hour; during the anodization process, condensed water is used to control the temperature of the anodized solution at 10°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0055] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 48 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0056] Example 4
[0057] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S3, the anodization time is replaced from 1 h to 2 h, and comprises the following steps:
[0058] S1. A nickel mesh with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel mesh was rinsed with deionized water until the pH value was 7. The washed nickel mesh was stored in anhydrous ethanol for later use.
[0059] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.54 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0060] S3. In a double-electrode electrolytic cell, the nickel mesh is used as the anode and the platinum sheet is used as the cathode. The nickel mesh is anodized by anodization method; a DC regulated power supply is used to control the anodization voltage to 50V, and the anodization is performed for 1 hour; during the anodization process, condensed water is used to control the temperature of the anodized solution at 10°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0061] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 48 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0062] Example 5
[0063] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S3, the anodization time is replaced from 1 h to 8 h, and comprises the following steps:
[0064] S1. A nickel mesh with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel mesh was rinsed with deionized water until the pH value was 7. The washed nickel mesh was stored in anhydrous ethanol for later use.
[0065] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.54 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0066] S3. In a double-electrode electrolytic cell, the nickel mesh is used as the anode and the platinum sheet is used as the cathode. The nickel mesh is anodized by anodization method; a DC regulated power supply is used to control the anodization voltage to 50V, and the anodization is performed for 1 hour; during the anodization process, condensed water is used to control the temperature of the anodized solution at 10°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0067] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 48 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0068] Example 6
[0069] A method for preparing a ruthenium-doped nickel-based catalyst electrode has the same preparation steps as those in Example 1, except that in step S4, the immersion time is replaced from 48 h to 24 h, to obtain a ruthenium-doped nickel-based catalyst electrode, recorded as ANM-Ru-24.
[0070] Example 7
[0071] A method for preparing a ruthenium-doped nickel-based catalyst electrode has the same preparation steps as those in Example 1, except that in step S4, the immersion time is replaced from 48 h to 12 h, thereby obtaining a ruthenium-doped nickel-based catalyst electrode, which is recorded as ANM-Ru-12.
[0072] Example 8
[0073] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S3, the temperature of the anodizing solution is replaced from 10° C. to 0° C., comprises the following steps:
[0074] S1. A nickel mesh with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel mesh was rinsed with deionized water until the pH value was 7. The washed nickel mesh was stored in anhydrous ethanol for later use.
[0075] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.54 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0076] S3. In a double-electrode electrolytic cell, the nickel mesh is used as the anode and the platinum sheet is used as the cathode. The nickel mesh is anodized by anodization method; a DC regulated power supply is used to control the anodization voltage to 50V, and the anodization is performed for 1 hour; during the anodization process, condensed water is used to control the temperature of the anodized solution at 0°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0077] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 24 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0078] Example 9
[0079] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S3, the temperature of the anodizing solution is changed from 10° C. to 20° C., comprising the following steps:
[0080] S1. A nickel mesh with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel mesh was rinsed with deionized water until the pH value was 7. The washed nickel mesh was stored in anhydrous ethanol for later use.
[0081] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.54 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0082] S3. In a double-electrode electrolytic cell, the nickel mesh is used as the anode and the platinum sheet is used as the cathode. The nickel mesh is anodized by anodization method; a DC regulated power supply is used to control the anodization voltage to 50V, and the anodization is performed for 1 hour; during the anodization process, condensed water is used to control the temperature of the anodized solution at 20°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0083] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 24 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0084] Example 10
[0085] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S1, the nickel-based substrate is replaced by nickel foam instead of nickel mesh, and comprises the following steps:
[0086] S1. Ultrasonicate a nickel foam having a size of 1 cm×1 cm in a 3 mol / L hydrochloric acid solution for 10 min, then rinse the ultrasonicated nickel foam with deionized water until the pH value is 7, and store the washed nickel foam in anhydrous ethanol for later use.
[0087] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.54 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0088] S3. In a double-electrode electrolytic cell, the nickel foam is used as the anode and the platinum sheet is used as the cathode to anodize the nickel foam; a DC regulated power supply is used to control the anodizing voltage to 50 V and anodize for 1 hour; during the anodizing process, condensed water is used to control the temperature of the anodizing solution at 10°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0089] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 48 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0090] Embodiment 11
[0091] A method for preparing a ruthenium-doped nickel-based catalyst electrode, which has the same preparation steps as those in Example 1, except that in step S1, the nickel-based substrate is replaced by a nickel plate instead of a nickel mesh, and comprises the following steps:
[0092] S1. A nickel plate with a size of 1 cm×1 cm was ultrasonically treated in a 3 mol / L hydrochloric acid solution for 10 min, and then the ultrasonicated nickel plate was rinsed with deionized water until the pH value was 7. The washed nickel plate was stored in anhydrous ethanol for later use.
[0093] S2. Ethylene glycol and glycerol were mixed in a volume ratio of 1:3, distilled water was added to the mixed solution to make the water concentration 3 mol / L, and then solid ammonium fluoride was added to make the concentration 0.54 mol / L, and stirring was continued for 24 hours to obtain a completely uniform anodizing solution.
[0094] S3. In a double-electrode electrolytic cell, the nickel plate is used as the anode and the platinum sheet is used as the cathode to perform an anodizing treatment on the nickel plate; a DC regulated power supply is used to control the anodizing voltage to 50 V and anodize for 1 hour; during the anodizing process, condensed water is used to control the temperature of the anodizing solution at 10°C to obtain a nickel-based catalyst electrode; the nickel-based catalyst electrode is then rinsed with deionized water and dried for use.
[0095] S4. After immersing the nickel-based catalyst electrode in a 5 mmol / L RuCl3 solution for 48 hours, the nickel-based catalyst electrode was rinsed with deionized water and dried in an oven at 60°C for 24 hours to obtain a ruthenium-doped nickel-based catalyst electrode.
[0096] Figure 1 This is an electron microscope image of the nickel-based catalyst electrode in Example 1 of the present invention. Figure 1 It is concluded that the surface of the nickel-based nickel mesh of the present invention presents a pore structure after anodization, and the pore diameter is about 500nm; due to the presence of the porous nickel oxyhydroxide catalyst layer, ruthenium ions are more likely to penetrate into these pores and replace and dope with nickel ions. Therefore, the pore structure can not only increase the surface area of the ruthenium-doped nickel-based catalyst electrode, but also promote the doping of ruthenium elements.
[0097] The NM, ANM, ANM-Ru-48 prepared in Example 1 and the ANM-Ru-24 prepared in Example 6 were respectively used as working electrodes, the Hg / HgO electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. One end of the working electrode, the reference electrode and the counter electrode was placed in a 1 mol / L potassium hydroxide solution, and the other ends were electrically connected to an electrochemical workstation (CHI660E). The HER and OER polarization curves of the electrodes were tested at a scan rate of 5 mV / s. The test results are as follows:
[0098] Figure 2LSV curves of HER of NM, ANM, ANM-Ru-48 prepared in Example 1 of the present invention and ANM-Ru-24 prepared in Example 6 and their corresponding overpotential diagrams, wherein (a) is the LSV curve of HER of NM, ANM, ANM-Ru-48 prepared in Example 1 and ANM-Ru-24 prepared in Example 6, and (b) is the overpotential diagram of NM, ANM, ANM-Ru-48 prepared in Example 1 and ANM-Ru-24 prepared in Example 6. Figure 2 (a) It is concluded that the nickel-based catalyst electrode obtained after anodization has a lower hydrogen evolution starting potential and a higher current density than the nickel-based nickel mesh; the hydrogen evolution starting potential of the ruthenium-doped nickel-based catalyst electrode is further reduced compared to the hydrogen evolution starting potential of the nickel-based catalyst electrode, and the current density is further improved; Observation Figure 2 (b) It is concluded that the HER overpotential of the nickel-based nickel mesh is very large, at 340.5mV; the overpotential of the nickel-based catalyst electrode obtained after anodization treatment is reduced to 271.7mV; after successful doping with ruthenium, the overpotential of the ruthenium-doped nickel-based catalyst electrode is further reduced. After the nickel-based catalyst electrode is immersed in a ruthenium-containing solution for 48h, the HER overpotential of ANM-Ru-48 is reduced to 80.9mV.
[0099] Figure 3 LSV curves of OER of NM, ANM, ANM-Ru-48 prepared in Example 1 of the present invention and ANM-Ru-24 prepared in Example 6 and their corresponding overpotential diagrams, wherein (a) is the LSV curve of OER of NM, ANM, ANM-Ru-48 prepared in Example 1 and ANM-Ru-24 prepared in Example 6, and (b) is the overpotential diagram of OER of NM, ANM, ANM-Ru-48 prepared in Example 1 and ANM-Ru-24 prepared in Example 6. Figure 3 (a) It is concluded that the nickel-based catalyst electrode obtained after anodization has a lower oxygen evolution starting potential and a higher current density than the nickel-based nickel mesh; after doping with ruthenium, the oxygen evolution starting potential of the ruthenium-doped nickel-based catalyst electrode is further reduced compared with the hydrogen evolution starting potential of the nickel-based catalyst electrode, and the current density is further improved; Observation Figure 3 (b) It is concluded that the OER overpotential of the nickel-based nickel mesh is very large, at 683.7mV; the overpotential of the nickel-based catalyst electrode obtained after anodization treatment is reduced to 616.8mV; after successful doping with ruthenium, the overpotential of the ruthenium-doped nickel-based catalyst electrode is further reduced. When the nickel-based catalyst electrode is immersed in a ruthenium-containing solution for 48h, the OER overpotential of ANM-Ru-48 is reduced to 490.2mV.
[0100] The test of the overall water splitting performance adopts a two-electrode system, with the ruthenium-doped nickel-based catalyst electrode of Example 1 as the anode and cathode, and the polarization curve of the electrode is tested in a 1 mol / L potassium hydroxide solution at a scanning rate of 5 mV / s. After the electrochemical test, all potentials are converted to the potential relative to the reversible hydrogen electrode.
[0101] Figure 4 The ruthenium-doped nickel-based catalyst electrode in Example 1 of the present invention is used as the anode and cathode at 1000 mA / cm 2 Voltage-time diagram of water electrolysis at different current densities. Figure 4 It is concluded that in 1 mol / L potassium hydroxide solution, 1000 mA / cm 2 The cell voltage can remain stable when water is electrolyzed for up to 500 hours at the current density.
[0102] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a ruthenium-doped nickel-based catalyst electrode, characterized in that: The following steps are involved: Dissolving a fluoride-containing ion salt in a mixture of ethylene glycol and glycerol, and then mixing with water to obtain an anodizing solution; wherein the volume ratio of the ethylene glycol to the glycerol is 1:2-4; and the concentration of the fluoride-containing ion salt in the anodizing solution is 0.25 mol / L-0.8 mol / L; The nickel-based substrate is placed in an anodizing solution for anodizing treatment. During the anodizing treatment, nickel atoms on the surface of the nickel-based substrate are combined with hydroxide ions in the anodizing solution under the etching of fluorine-containing salts and the oxidation of the electric field, thereby forming a porous nickel oxyhydroxide catalyst layer on the surface of the nickel-based substrate to obtain a nickel-based catalyst electrode; The nickel-based catalyst electrode is immersed in a solution containing ruthenium element. During the immersion process, ruthenium ions are replaced and doped with nickel ions in the porous nickel hydroxide oxycatalytic layer. After drying, a ruthenium-doped nickel-based catalyst electrode is obtained.
2. The method for preparing a ruthenium-doped nickel-based catalyst electrode according to claim 1, characterized in that: The fluoride-containing ion salt is selected from one or both of ammonium fluoride and sodium fluoride.
3. The method for preparing a ruthenium-doped nickel-based catalyst electrode according to claim 1, characterized in that: The method of anodizing is: The nickel-based substrate is anodized with an anodizing solution as electrolyte, a nickel-based substrate as anode, a platinum sheet as cathode, and a DC regulated power supply connected to obtain a nickel-based catalyst electrode.
4. The method for preparing a ruthenium-doped nickel-based catalyst electrode according to claim 3, characterized in that: The anodizing treatment conditions are: anodizing at 0°C to 20°C, 20V to 50V, for 1h to 8h.
5. The method for preparing a ruthenium-doped nickel-based catalyst electrode according to claim 1, characterized in that: The nickel-based substrate is selected from nickel mesh, nickel foam, nickel plate or metallic nickel.
6. The method for preparing a ruthenium-doped nickel-based catalyst electrode according to claim 1, characterized in that: The concentration of the ruthenium element solution is 5mmol / L to 10mmol / L.
7. The method for preparing a ruthenium-doped nickel-based catalyst electrode according to claim 1, characterized in that: The ruthenium-containing solution is selected from RuCl3 solution.
8. The method for preparing a ruthenium-doped nickel-based catalyst electrode according to claim 1, characterized in that: The immersion time is 12 hours to 48 hours.
9. A ruthenium-doped nickel-based catalyst electrode prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The ruthenium-doped nickel-based catalyst electrode is composed of a ruthenium-doped nickel-based catalyst and a nickel-based substrate, and the ruthenium-doped nickel-based catalyst is loaded on the nickel-based substrate.
10. Use of the ruthenium-doped nickel-based catalyst electrode according to claim 9 in preparing a cathode hydrogen evolution electrode and an anode oxygen evolution electrode.